2005
DOI: 10.1063/1.2093936
|View full text |Cite
|
Sign up to set email alerts
|

Empirical correlation finding the role of temperature and particle size for nanofluid (Al2O3) thermal conductivity enhancement

Abstract: In this letter, we report an experimental correlation [Eqs. (1a) and (1b) or (1c)] for the thermal conductivity of Al2O3 nanofluids as a function of nanoparticle size (ranging from 11nmto150nm nominal diameters) over a wide range of temperature (from 21to71°C). Following the previously proposed conjecture from the theoretical point-of-view (Jang and Choi, 2004), it is experimentally validated that the Brownian motion of nanoparticles constitutes a key mechanism of the thermal conductivity enhancement with incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

31
520
1
11

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 1,074 publications
(563 citation statements)
references
References 14 publications
31
520
1
11
Order By: Relevance
“…Fig. 9 Comparison with previously reported work and our proposed work on temperature-dependent nanofluid thermal conductivity ratio for alumina nanofluid (Maxwell 1954;Hamilton and Crosser 1962;Wang et al 2008;Beck et al 2009;Moghadassi et al 2010;Kleinstreuer and Feng 2011;Chon et al 2005;Li and Peterson 2006) Due to the particle volume concentration the dynamic viscosity of nanofluid has been increased and as temperature increases viscosity decreases, which is concluded by Nguyen et al (Nguyen et al 2008;Chandrasekar et al 2010). This process is the witness for the particle suspension beyond the critical temperature, which caused by the hysteresis phenomenon.…”
Section: Effective Viscosity Of Nanofluidmentioning
confidence: 61%
See 1 more Smart Citation
“…Fig. 9 Comparison with previously reported work and our proposed work on temperature-dependent nanofluid thermal conductivity ratio for alumina nanofluid (Maxwell 1954;Hamilton and Crosser 1962;Wang et al 2008;Beck et al 2009;Moghadassi et al 2010;Kleinstreuer and Feng 2011;Chon et al 2005;Li and Peterson 2006) Due to the particle volume concentration the dynamic viscosity of nanofluid has been increased and as temperature increases viscosity decreases, which is concluded by Nguyen et al (Nguyen et al 2008;Chandrasekar et al 2010). This process is the witness for the particle suspension beyond the critical temperature, which caused by the hysteresis phenomenon.…”
Section: Effective Viscosity Of Nanofluidmentioning
confidence: 61%
“…Kleinstreuer and Feng (2011) established relationship between thermal conductivity and some fundamental parameters like concentration, temperature, particle size which are exceptionally valuable for a nanofluid. Chon et al (2005) reported the inversely dependence of particle size on thermal conductivity upgrade, considering distinctive sizes of alumina nanoparticles suspended in water base fluid. Another basic model is given by Li and Peterson (2006) where they explain thermal conductivity expressions correspond to temperature and concentration by using curve fitting for Al 2 O 3 -water nanofluids.…”
Section: Thermal Conductivity Of Nanofluidmentioning
confidence: 99%
“…% of nanoparticles such as alumina (Al 2 O 3 ), copper oxide (CuO), and copper (Cu) dispersed in different base fluids, the thermal conductivity of the nanofluids was observed a significant improvement ($60%) as compared to the corresponding base fluids. The results also clearly show that the thermal conductivity of the nanofluid depends on the nanoparticle volume fraction, [6,7] the size and the shape. [8,9] Assuming that the sphericity of copper nanoparticles is of 0.3, the thermal conductivity of water can be enhanced by a factor of 1.5 at the nanoparticle volume fraction of 5%.…”
Section: Introductionmentioning
confidence: 71%
“…Therefore, more comprehensive data are required before concluding whether the thermal conductivity exhibits a linear relationship with temperature. Chon et al [21] reported thermal conductivity measurements of water containing Al 2 O 3 nanoparticles at temperatures between 21 and 71ºC. They observed that the thermal conductivity increased as the temperature increased.…”
Section: Effect Of Temperaturementioning
confidence: 98%
“…At low concentrations, the slope was greater than at high concentrations. Most thermal conductivity data in the literature for Al 2 O 3 -water nanofluids showed that with increasing nanoparticle volume concentration, the thermal conductivity also increased [21][22][23][24][25][26][27][28][29][30], however, the intensity of the increase decreased for the larger volume concentrations.…”
Section: Effect Of Volume Concentrationmentioning
confidence: 99%